BOREHOLE GEOPHYSICAL TECHNIQUES TO DEFINE STRATIGRAPHY, ALTERATION AND AQUIFERS IN BASALT - Helm-Clark C.M.; Rodgers D.W.; Smith R.P. (My University, 2004)
This paper concerns the interpretation of borehole geophysical data from basalt sequences, especially continental basalt sequences that host aquifers. Based on modifications of the rules used for interpreting borehole data from sedimentary rocks, new rules are proposed to identify the internal stratigraphy, aquifer boundaries, and alteration features in continental basalts.The value of several wireline tools is critiqued. Natural gamma logs have limited utility in basalt sequences unless anomalously high-potassium or low-potassium basalt flows and/or sedimentary interbeds exist which can act as marker beds for stratigraphic correlations. Neutron logs can usually discriminate between individual flows, flow breaks and interbeds, even in unsaturated basalts. Neutron logs and temperature logs can also be used to map aquifer thickness in basalt. Gamma-gamma density logs are usually sensitive to the density contrasts between interbeds and basalt flows, and in combination with neutron and natural gamma logs are crucial for the correct interpretation of large void spaces in basalt such as collapsed lava tubes and formerly inflated pahoehoe lobes. Basalt porosity calculated from neutron, resistivity and/or gamma-gamma density logs is commonly overestimated due to the presence of hydrous alteration minerals. Velocity and resistivity logs are best at discriminating between flows in saturated conditions. Magnetic susceptibility logs may capture magnetic mineralogy variations at a finer scale than that of flows and flow breaks and therefore should always be interpreted in combination with other logs. Non-spectral neutron-gamma logs are not useful in basalt, though spectral neutron-gamma logs have been used successfully for stratigraphic correlation and to locate pollutants. Geochemical logs or the inclination of magnetic remanence provide the best data to discriminate individual flows with a basalt sequence, and thus establish an internal stratigraphy. Other tools used alone cannot provide reliable stratigraphic information, but a combination of tools may work. We recommend the combination of natural gamma, neutron, and gamma-gamma density logs in unsaturated rocks, and these logs plus velocity and resistivity logs in saturated rocks.
Keywords: BOREHOLE GEOPHYSICS; BASALT AQUIFERS